Peace Data Standard: A Practical and Theoretical Framework for Using Technology to Examine Intergroup Interactions - Guadagno, Rosanna E.; Nelson, Mark; Lock Lee, Laurence (Frontiers in Psychology, 2018)
The present paper presents a theoretical framework for standardizing Peace Data as a means of understanding the conditions under which people's technology use results in positive engagement and peace. Thus, the main point of our paper is that Big Data can be conceptualized in terms of its value to peace. We define peace as a set of positive, prosocial behaviors that maximize mutually beneficial positive outcomes resulting from interactions with others. To accomplish this goal, we present hypothetical and real-world, data driven examples that illustrate our thinking in this domain and present guidelines for how to identify, collect, utilize, and evaluate Peace Data generated during mediated interactions and further suggest that Peace Data has four primary components: group identity information, behavior data, longitudinal data, and metadata. This paper concludes with a call for participation in a Peace Data association and suggested for guidelines for how scholars and practitioners can identify Peace Data in their own domains. Ethical considerations and suggestions for future research are also discussed.